From pests to tests: training rats to diagnose tuberculosis. Issue 3 (19th March 2020) - Fiebig, Lena; Beyene, Negussie; Burny, Robert; Fast, Cynthia D.; Cox, Christophe; Mgode, Georgies F.
2020 is the year of the rat. The rat is the first of the 12 Chinese zodiac signs, and represents spirit, alertness, flexibility and vitality. In respiratory medicine, we may think of rats as vectors for diseases, such as pulmonary forms of hantavirus disease or leptospirosis, and pneumonic plague. Rodent control is thus part of hygiene guidelines and the International Health Regulations. And yet, the rat's keen sense of smell has led to its incredible career as a living tuberculosis (TB) detector. It's time… to find and treat all patients with TB. Rats may have a say in research towards better diagnostic tests. http://bit.ly/2Rioa9N